2016
DOI: 10.18632/aging.100967
|View full text |Cite
|
Sign up to set email alerts
|

Reduced SOD2 expression is associated with mortality of hepatocellular carcinoma patients in a mutant p53-dependent manner

Abstract: The development and progression of hepatocellular carcinoma (HCC) is accompanied with persistent oxidative stress, but the molecular basis is not well defined. Superoxide dismutase 2 (SOD2) is an important mitochondrial antioxidant and a key aging factor. Here we investigated the expression and clinical significance of SOD2 in a large cohort of HBV-positive HCC tumors. Both SOD2 mRNA and protein are reduced in human primary HCCs compared with matching liver tissues. Consistently, the SOD2 DNA copy numbers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…Among SOD family members, manganese superoxide dismutase 2 (MnSOD‐ SOD2 ) plays an essential role not only in cancer but also in a wide range of stress‐induced diseases due to its localization in the mitochondria, where the production of ROS is higher compared to the other cellular compartments (Inoue et al ., ). In particular, SOD2 has been described as a tumor suppressor gene (Van Remmen et al ., ) and its decreased expression level has been reported in a wide variety of diseases (Wang et al ., ) (Hitchler et al ., ), including hematological malignancies (Hurt et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among SOD family members, manganese superoxide dismutase 2 (MnSOD‐ SOD2 ) plays an essential role not only in cancer but also in a wide range of stress‐induced diseases due to its localization in the mitochondria, where the production of ROS is higher compared to the other cellular compartments (Inoue et al ., ). In particular, SOD2 has been described as a tumor suppressor gene (Van Remmen et al ., ) and its decreased expression level has been reported in a wide variety of diseases (Wang et al ., ) (Hitchler et al ., ), including hematological malignancies (Hurt et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Two-tailed Student's t-test: **P < .01 versus untreated cells; *P < .05 versus untreated cells. SOD2 has been described as a tumor suppressor gene (Van Remmen et al, 2003) and its decreased expression level has been reported in a wide variety of diseases (Wang et al, 2016) (Hitchler et al, 2008, including hematological malignancies (Hurt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SOD2 contributes to the regulation of cell proliferation, transformation, migration, invasion and angiogenesis primarily through the redox-dependent modulation of the transcription factors NF-KB, HIF-1, AP-1 and p53 100,102104 . SOD2 deficiency has been shown to have both pro- and antitumorigenic activity 102,105107 . High SOD2 expression can inhibit cell proliferation directly 108 or sensitize cells to the cytotoxicity of the anti-cancer drugs 109 .…”
Section: Sod2 / Mnsod2mentioning
confidence: 99%
“…There is a reduction in the mRNA and protein expressions for Mn‐SOD (SOD2) in HCC patients, and that there is a close relationship between low SOD2 levels with p53 mutations in these patients (Wang, Yin et al, ) (Figure ). During hepatocarcinogenesis, upregulation of mitochondrial Ca 2+ uniporter (MCU) increases Ca 2+ uptake toward mitochondria by down‐regulating the ratio for nicotinamide adenine dinucleotide + (NAD + ) to its reduced form (nicotinamide adenine dinucleotid (NADH).…”
Section: Introductionmentioning
confidence: 99%